Outlooks on poverty: a conceptual approximation (2015)
In this article several definitions or concepts are presented for the understanding, measuring and analyzing of poverty. For this, the written productions of different scholars and researchers who have made valuable contributions to the subject are returned to. In addition to these concepts, the different perspectives used to approach the study of poverty are analyzed, although these are not theories or explanations of its causes, but rather views of poverty that reflect these approaches. Likewise, the study develops a review of the methodologies most used in the identification and aggregation processes. Finally, public policies in the social sectors are interpreted.